(3TQM Yjhf GdEYQGHs - (3CHhGdMSf Ydj Hf aVGd Hf Ydj GdeLGTYj GdaQRObjs; (3CHheMeO YHjOGddg Hf CMeO GdZRGQj GdHUQj,J (B381 (3g` ? s ((3eMeO Hf Ydj GdfSGL s)
(3ChdgG (B:s
(3hHYO, aEf GdYdhe Yde jYQa Hg MbGFb GdeYGfj hjhba Hg Ydi GdCUhd hGdeHGfj s
(3BNQgG (B:s
(3aEf YVO Pdc SeGY aj efKhQ GdcdGe Med Ydi gPG h EdG aGdhLg GdQaY deG PcQfGg Je GdcJGH s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3egedI GdfbW bdjdkGs
(3ajg VHWs
(3hbO fSNgG GdfGSN ef fSNI ecJhHI ef fSNI bQFJ Ydi eUfagGs
(3hGdfSNI ebGHdI s
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
Keywords: (3GdfMhs